Crossing borders : international exchange and planning practices - Healey, Patsy; Upton, Robert, 1951- (RTPI library series ;, 2010)
Takes a critical look at the international diffusion of planning ideas and practices, their impacts on planning practices in different contexts, on the challenge of 'situating' planning practices, and on the ethical and methodological issues of international exchange in the planning field.